About the Master’s Program “Creative Personnel Management”: Methodological Foundations - A. O. Grudzinskiy; I. V. Guskova; N. E. Serebrovskaya; V. V. Mariko (Высшее образование в России)
In order to improve the training of masters majoring in “Personnel Management”, a sociological study of the opinions of employers was carried out. Based on the results of the study, HRtechnologies were clarified and the content of professional competencies, which should be possessed by specialists in HRM departments of organizations and enterprises who belong to the category of creative personnel, was disclosed. The main driving force behind the growth of innovative economies of developed and developing countries is a social group of people characterized by a high level of education, creative abilities and entrepreneurial behavior skills. This social group is called the “creative class”. The general criteria for classifying employees as creative personnel are defined. At the preliminary stage of the study, the Federal State Educational Standard of Higher Education 38.04.03 “Personnel Management (Master’s level)” was analyzed as well as the requirements of a professional standard for a HRM specialist. To study the opinions of employers, a two-stage study was carried out. At the first stage, a focused interview with senior management staff was carried out in order to find out the practical methods of working with creative staff (N = 43). The working hypothesis was the assumption that there is a significant specificity in the processes of attracting, developing and retaining creative staff. The results of the processing of interview texts are presented. Based on the interview, a list of professional competencies was prepared, the possession of them can improve the quality of creative staff management. At the second stage, a questionnaire survey was conducted among a wider group of employers with the task of determining the priority of the proposed professional competencies (N=87). Interviews and questionnaires were conducted with representatives of human resources and the management team of enterprises and organizations (including higher education institutions) of Nizhny Novgorod, whose main activity is aimed at obtaining an intellectual product. Two senior employees of one of the largest startups in Silicon Valley (USA) were among the interviewees. The authors, with the support of the Vladimir Potanin Scholarship Program, have developed a master’s program in Creative Human Resources Management. Based on the results of the study, appropriate adjustments were made to the work programs of the disciplines and to the list of professional competencies of the developed master’s program, which determine its orientation.